Dialogic Reading to Promote the Underprivileged Pre-School Children's Expressive Language Ability - Andi Asrifan; Iwan Setiawan; Maria Teodora Ping; Syamdianita Syamdianita; Nur Fadillah Nurchalis (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Background: Children from low socioeconomic backgrounds in Indonesia have been facing challenges in terms of their literacy and language development. One of the possible reasons is that they are not used to receiving meaningful early reading interventions such as shared reading during their pre-school attendance. This phenomenon has brought to light the urgency of having an early intervention, which can accommodate the very diverse linguistic and cultural context of Indonesia- a multilingual and multicultural country. Methodology: This study employed an explanatory sequential mixed-method research design. The first phase was conducted in a quantitative one-group pre-experiment with pre-and post-test design. The second phase of this research was carried out in a qualitative case study through classroom observation and informal interviews with the teacher and the children. Findings: The findings of MLU calculation showed that for the pre-test, the mean score was 2.35, the median was 2.20 and the standard deviation was 0.53. Meanwhile, for the post-test, the mean score was 3.72, the median was 3.18 and the standard deviation was 1.38. The qualitative phase explored two main aspects, namely the implementation of dialogic reading activity by the teacher and the teacher as well as children’s opinions regarding the dialogic reading activity. Conclusion: This current study has offered an insight that dialogic reading activity could be well implemented by the teacher in a typical Indonesian pre-school setting. The dialogic reading activity was also found to contribute significantly to the development of children’s expressive language ability. Originality: The findings of this study have indicated dialogic reading potentials in terms of promoting children’s language development and just as importantly, sparking children’s joy of reading since their early years of formal education. Therefore, it is suggested that early childhood educators and parents work hand in hand to incorporate dialogic reading activity into their daily literacy practices at schools as well as at home.